Pengaruh Kebijakan Politik Etis Pemerintah Kolonial Belanda Terhadap Keberadaan Lembaga Pendidikan Islam di Nusantara - Suci Karlina Aziz; Lidin Wiwah Jaya Putra; Kasful Anwar US; Sya'roni Sya'roni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The study of this paper discusses the ethical political policy of the Dutch colonial government towards the existence of Islamic educational institutions in the archipelago, the discussion of the research of this paper to find out how the history of the existence of Islamic educational institutions in the archipelago, the ethical politics of the Dutch colonial government, and the influence of ethical political policies on Islamic educational institutions. Islamic education in Indonesia has emerged and developed in various forms of various institutions, such as Islamic boarding schools, madrasas, surau, and musholah. In its development, Islamic education in Indonesia is characterized by the emergence of various educational institutions gradually, ranging from very simple ones, to stages that are considered modern and complete. The goal is not only to enrich the treasures of science with Islamic nuances, but also as a reference and comparison material for Islamic education managers in the following periods. This is in line with the principle generally adopted by the Indonesian Islamic community, which is to maintain the good traditions of the past and take new good traditions again. In this way, the efforts to develop Islamic educational institutions will not be radically rooted in their culture. The ethis politics or the politics of revenge of the Dutch colonial government to the Indonesian colonial people is a policy of the Dutch royal government to repay the sacrifices of the Indonesian people during the implementation of the cultuur stelsel or forced planting system. the people of the archipelago.